Diversity and Research in Spanish Universities. Weaknesses, Strengths, and Good Practices for Inclusive Research - Hernández-Lloret, Carmen-María; Álvarez-Castillo, José-Luis; Espino-Díaz, Luis; González-González, Hugo; Fernández-Caminero, Gemma (Journal of Education Culture and Society, 2024)
Aim. Diversity and inclusion are part of the third mission of higher education institutions. One of the dimensions that must be considered in the process of institutionalising inclusion is research. Inclusive research allows for critical research and reflection on certain fundamental issues on the road to democratic citizenship, making a positive impact on people's lives while contributing to social change and transformation. However, the literature has evidenced barriers in the institutionalisation effort, such as those posed by the market conception. In this context, the study presented here analyses the involvement of higher education research with diversity, as well as its weaknesses and strengths, and finally contributes to the identification of proposals for improvement and good practices for inclusive research.Methods. This work was based on assumptions of the interpretative paradigm, using virtual, one-on-one, semi‐structured interviews with Spanish researchers from different universities –most of them leading national projects on inclusion.Results. The results show that research on diversity is beginning to be incorporated as an essential modality in university agendas. In parallel, it is thought that academic capitalism and competitiveness have pierced conceptions of research quality, and in doing so, diversity and inclusion principles are called into question.Conclusions. Currently, the strengths of inclusion research in higher education are not as robust as the weaknesses. Proposals are made for the improvement of inclusive and democratic research, and four principles are set out to promote the institutionalisation of research on inclusion in universities.